Determinants of Career Maturity of Final-Year Undergraduates in Selected Malaysian Private Higher Education Institutions - See, Boon Ping (2009)
The study was conducted to identify the determinants of career maturity among undergraduates in private higher education institution in Malaysia. In this study, the level of career maturity was being identified and its relationships with gender, social-economic status, work experience, work value, Career Decision-making Self-efficacy and self-esteem were being studied. The targeted samples were 340 final year undergraduates from two selected private higher education institutions. Out of this total, 275 responded and data was collected for analysis and interpretations. In order to identify the relationships and differences of independent variables, Pearson’s Product-Moment Correlation test, independent sample t-test and ANOVA test have been carried out with level of career maturity. Meanwhile, multiple linear-regression analysis was done with its independent variables in order to identify the determinants of career maturity in this study. Overall, it was found that the career maturity was at upper moderate level (M = 3.6393). There were no significant differences on mean career maturity level by gender, SES and work experience (p > .05). It was found that SES, work value, Career Decision-making Self-efficacy and self-esteem were significantly related to career maturity (p < .05). Among these independent variables, CDMSE had scored the highest Pearson’s correlation coefficient value (r = .610, p < .0125). It is then followed by self-esteem (r = .374, p < .05), work value (r = .234, p < .05) and SES (r = .158, p < .05). In this study, the significant determinants for career maturity were CDMSE (t = 9.438, p < .05) and self-esteem (t = 2.495, p < .05). On the other hand, the SES (t = 1.448, p > .05) and work value (t = .279, p > .05) were not significant determinants for career maturity in this study. The regression model was not fully supported by the data collected. Only about 38% of the variability in career maturity was explained by the four independent variables. Based on the findings of this study, further research is needed to identify additional determining variables, and to improve the regression model of career maturity. Suggestions for implement and develop for suitable career development programmes were discussed.